THE SUPERHEROES of CYBERSPACE: Help Desk Careers. - Easom, Colin (Career Planning & Adult Development Journal)
The article focuses on the importance of help desk for information technology due to for technical troubleshooting with a problem-solving techniques in cyberspace. It mentions variety of support tickets relating to email accounts, smart phone apps, learning management systems, ebooks and tablets. It also mentions problem in the online classroom faced by students and teachers.